2018
DOI: 10.1186/s12864-018-4962-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with olive mill wastewaters induces modifications on chicken jejunum epithelial cell transcriptome and modulates jejunum morphology

Abstract: BackgroundThe Mediterranean diet is considered one of the healthier food habits and olive oil is one of its key components. Olive oil polyphenols are known to induce beneficial effects in several pathological conditions, such as inflammatory bowel disease, and to contrast the proliferation of cancer cells or hypercholesterolemia. Polyphenols are also present in waste products derived from the olive industry: olive mill wastewaters (OMWW) are rich in polyphenols and there is an increasing interest in using OMWW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…Enlarged crypt depth is indicative of increased turnover of intestinal epithelium in response to tissue damage. [50][51][52] In addition, structural changes were noted in both the cecum and proximal colon as the number of crypts increased with chronic SF. Currently, not much is known regarding the effect of increased crypts.…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged crypt depth is indicative of increased turnover of intestinal epithelium in response to tissue damage. [50][51][52] In addition, structural changes were noted in both the cecum and proximal colon as the number of crypts increased with chronic SF. Currently, not much is known regarding the effect of increased crypts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the phenols and polyphenols contained in olive oil by-products have antibacterial activity against Gram-positive bacteria like Staphylococcus aureus and Gram-negative bacteria like Campylobacter spp. [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Olive mill wastewater-a waste product obtained during olive oil extraction-is rich in polyphenols and has already been used in chicken feeding. Its effect on the transcriptome profile of jejunum has also been investigated by Sabino et al (2018b), who found that, in epithelial cells of the jejunum, 280 genes were differentially expressed in birds fed the experimental diet. The downregulated genes were mostly associated with the PPAR signaling pathway, with steroid biosynthesis, and with lipid metabolisms; the upregulated genes were involved in the regulation of viral processes (such as viral replication and viral regulation of the life cycle).…”
Section: Supplementation With Plant Origin Extractsmentioning
confidence: 99%